Effect of using recycled aggregates as road subbase materials: A case study from Kuwait City - Esraa A. Al-Ali; Waleed K. Eid (Kuwait Journal of Science)
In the State of Kuwait, the rise of the construction industry increases the construction and demolition activities and generates large amounts of aggregates. This study focuses on the use of recycled aggregates as road sub-base materials. Two different types of recycled aggregates have been used; namely, recycled concrete aggregates (RCA) and reclaimed asphalt pavement (RAP). Three mixtures are formed: control mix, RCA mix, and RAP mix. California Bearing Ratio (CBR) value was used as an acceptance criterion to evaluate the performance of the mixes. Results of CBR test were compared with the minimum limit of CBR value of road sub-base set by the Ministry of Public Work (MPW) specifications (MPW, 2012; section 3), (minimum 30%). The soaked CBR values of the control mix and RCA mix were equal to 73% and 80%, respectively, and they satisfy MPW specification (2012). While the soaked CBR value of RAP mix was equal to 29%, and it did not conform with MPW CBR limit for road sub-base (minimum 30%). The performance of RAP mix was enhanced by following two different scenarios. In the first scenario, the amount of RAP aggregates was decreased by mixing RAP with fresh aggregates. In the second scenario, cement was added to the RAP mix with two dosages, 2% and 4%. Both scenarios gave CBR values that meets the MPW requirement. It was concluded that RCA can be used as sub-base material, while RAP aggregates can be used as sub-base material when mixed with fresh aggregates or by adding cement as a modifier.